A New Rhodium/Copper-Cocatalyzed C–H Oxidation for the Preparation of Isoquinolin-1-ones - Zhou, Zeng-Le; Liu, Yi-Lin; Song, Jian-Lan; Deng, Chen-Liang (Synthesis, 2016)
A new and efficient rhodium/copper-cocatalyzed C–H oxidation reaction of isoquinolinium N-amides has been developed. In the presence of rhodium(II) acetate dimer, copper(II) chloride, a ligand and sodium tert-butoxide, a variety of isoquinolin-1-ones were prepared in moderate to good yields via ortho C–H oxidation.
Keywords: rhodium(II) acetate dimer; copper(II) chloride; isoquinolinium N-amides; C–H oxidation; isoquinolin-1-ones